Vigilância genômica dos arboviroses emergentes e reemergentes circulantes e co-circulantes no estado de Minas Gerais - Felipe Campos de Melo Iani (2021)
Despite the advances in modern medicine, infectious diseases are among the main causes of morbidity and mortality in the world, with arboviruses being responsible for most cases, mainly viruses of the Flaviviridae and Togaviridae families. The Zika virus and yellow fever of the genus Flavivirus belonging to the family Flaviviridae are a major threat to public health worldwide. Another virus of great medical importance is the chikungunya of the Togaviridae family responsible for major epidemics around the world. With the advancement of new generation genetic sequencing technology, it has been possible to carry out genomic surveillance to assist health authorities in combating epidemics caused by these emerging and reemerging viruses. In these works, 69 genomes of the Zika virus, 62 of the yellow fever virus and 20 genomes of the Chikungunya virus were sequenced, totaling 151 genomes. With the results of these genomic data associated with epidemiological data, it was possible to better characterize the epidemics that have occurred in recent years. The implementation of genomic surveillance in the public health laboratory of Minas Gerais made it possible to generate genomic data which, together with traditional epidemiological data and with the use of bioinformatics tools, made it possible to establish the evolutionary history and geographical spread over time of these arboviruses.